Self-concept and compensatory approaches applied to children with mild mental retardation - Lin, Chien-Chih (Leon) (Animo Repository, 2003)
This study assesses the self-concept of children with mild mental retardation (CWMMR) and correlated it with the compensatory approaches applied to them as perceived by their teachers and parents. Specifically, it seeks to find out the self-concept of CWMMR as peceived by their parents and teachers in terms of self-recognition, self-representation, self-description, self-assertion, self-evaluation, self-regulation and their positive and negative self-concepts. Likewise, the study determines the compensatory approaches to the CWMMR as perceived by their teachers and parents. The study employed the descriptive method of research utilizing a validated researcher-devised questionnaire. It involved 40 teachers and 40 parents of CWMMR in selected public and private special education centers in Quezon City. Findings showed that parents' perceived self concept of CWMMR were positive on self-recognition, self-regulation and self-evaluation, wherever teachers' perceived self concept of CWMMR were positive on self-recognition and self-representation, the rest were perceived negatively. Of the five compensatory approaches, four (visual arts, performing arts, sports/physical fitness and specialized skills) were perceived by parents and teachers to be applied sometimes. However, teachers' and parents perception on leisure and recreational activities were different (X=3.63 means often for teachers X=3.36 means sometimes for parents). The study further revealed that perceived Self-Concept of CWMMR for negligible correlation with that of the compensatory approaches for both teachers (r=0.16) and parents (r=0.02).